Shape-stabilized phase change composites supported by biomass loofah sponge-derived microtubular carbon scaffold toward thermal energy storage and electric-to-thermal conversion. (1st December 2022) - Song, Jiayin; He, Hongfei; Wang, Yibo; Shao, Liwen; Wang, Qingqing; Wei, Qufu; Cai, Yibing
Abstract: Integrating conductive carbon supports and organic phase change materials (PCMs) facilitates the development of thermal energy storage (TES) and conversion systems. Herein, we explore a novel phase change composite (PCC) based upon biomass-derived carbon scaffold incorporating polyethylene glycol (PEG) as a heat storage unit, which demonstrated a combination of good shape-stabilization, high thermal energy storage, and efficient electric-to-thermal conversion property. The carbon scaffold with a hollow microtubular structure was made from biomass loofah sponge (LS) through high-temperature carbonization in nitrogen. Compared with natural LS, the derived carbon scaffold exhibited favorable structural characteristics including a large specific surface area of 668.75 m 2 /g and a prominent micropore area of 303.37 m 2 /g, which could not only prevent PEG from leakage but also provide thermally and electrically conductive pathways in the PCM substance. The fabricated PCC displayed high thermal energy storage density (up to 137.6 J/g), outstanding electric-to-thermal conversion, enhanced thermal resistance, and robust temperature regulation properties. It provides an insightful strategy for fabrication and utilization of biomass-derived carbon scaffold based shape-stabilized PCCs in solar thermal energy storage, thermal management and thermoregulated textiles, and infrared stealth of important military targets, etc. Highlights: A novel PCC consisted of biomass-derived carbon scaffold and PEG was fabricated. Carbon scaffold had high adsorption capacity due to hollow microtubular structure. Carbon scaffold provided thermally and electrically conductive pathways. The fabricated PCC displayed high thermal energy storage density up to 137.6 J/g. PCC demonstrated enhanced thermal resistance and robust temperature regulation.